Using trail cameras to estimate free‐ranging domestic cat abundance in urban areas. Issue 6 (1st September 2016) - Elizondo, Elisa C.; Loss, Scott R.
Abstract : The domestic cat Felis catus is one of the most ecologically harmful invasive species on earth. Predation by free‐ranging cats poses a serious global threat to small vertebrates and is a leading source of anthropogenic mortality for birds and small mammals in North America. However, little is known about the size of cat populations, especially in urban areas where both cats and wildlife are abundant. Methods to quantify free‐ranging cat populations are needed to understand the magnitude of threats facing wildlife populations and to inform decisions about prioritizing conservation and cat population management. We assessed the utility of trail cameras and sight—resight analysis for estimating free‐ranging cat abundance in a small urban area (Stillwater, OK, USA). We also evaluated whether relationships exist between cat abundance and both urban development intensity and human population density. Even with relatively large cat populations, we identified the vast majority (∼96.5%) of individual cats in both day‐time and night‐time photos. We found no relationship between cat abundance and either urban development intensity or human population density. This finding combined with the large numbers of cats observed suggests that cats may be abundant in our study area regardless of urban context. Sampling freeranging cat populations across a broad range of urbanization intensities that capture a variety of human behaviors and/or cat management policies is needed to shed light on the drivers of cat population abundance. Trail cameras show promise as a highly useful tool for achieving this objective in the context of wildlife conservation management.